Insulin resistance in overweight and obese adolescents - Pajuelo, Jaime (2006)
Objective: To determine the presence of insulin resistance (IR) in a group of overweight and obese adolescents. Materials and Methods: One hundred 10 to 28 year-old children were studied, (77% females); 67% were overweight and the remaining obese. Overweight and obesity were determined by Must et al. criteria: overweight between 85 and 95 percentile and obesity overt the 95 percentile. Glycemia and basal insulin were determined in serum obtained by vein puncture. IR was determined by HOMA’s index considering Keskin diagnosis value of 3,1. Results: There was no biochemical statistical difference between the overweight and obesity groups; 14% showed IR, 16,2% in the obese children and 12,3% in those overweight. Average insulin and HOMA in obese children with IR were 315 uUl/mL and 7, respectively. The insulin and HOMA difference between those with and without IR was statistically significant. (p<0,0001). Waist circumference below the median was found in 16% with IR and 12% in the other group. Conclusions: Most of the overweight and obese adolescents in the group studied did not have insulin resistance and only 14% presented IR -16,2% in the obese and 12,3% in those overweight. The existence of IR in adolescents implies higher cardiovascular risk in those overweight and obese and requires preventive measures to face this problem.